Exploring Academic Reading Strategies Among EFL University Students: A Study at Tadulako University - Tribuana Puspitasari; Darmawan Darmawan; Andi Patmasari; Mochtar Marhum (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the reading strategies employed by seventh-semester students of the English Education Study Program at Tadulako University. This study employs a qualitative descriptive design aimed at exploring and analyzing the strategies used by students to comprehend academic texts. The data were collected through structured questionnaires administered to 21 students. The questionnaire includes statements rated on a Likert scale (from 1 = Never to 5 = Always). The findings reveal that while students frequently use strategies such as skimming, scanning, rereading, and using dictionaries to enhance comprehension, other strategies like summarizing, note-taking, and connecting ideas with prior knowledge are used. Moreover, many students rely on translation into their first language and assistance from friends, indicating ongoing challenges in processing academic texts in English. The study provides valuable insights for educators aiming to improve students reading comprehension on academic text.